Eficácia do teste de acidez graxa na avaliação da qualidade do café Arábica (Coffea arabica L.) submetido a diferente períodos e temperaturas de secagem - Marques, Elizabeth Rosemeire; Borem, Flavio Meira; Fonseca Alvarenga Pereira, Rosemary Gualberto; Martin Biaggioni, Marco Antonio [UNESP] (Universidade Federal de Lavras (UFLA), 2008)
This work had the aim of evaluating the effect of different temperatures and pre-drying periods on yard on the chemical composition and quality of the beverage of peeled cherry coffee. Temperatures of 40 degrees C, 50 degrees C and 60 degrees C were used in the mass with air flow of 20m(3)m(-1)m(2). After drying, the visible defects of the coffee samples were removed. For evaluation of quality, the following analyses were performed: sensorial analyses, total sugars, reducing sugars and non-reducing sugars, electrical conductivity, potassium leaching and fatty acidity. One verified that lower drying temperature and greater pre-drying period had contributed for the attainment of a better quality drink. The increase of temperature and pre-drying periods decreased the non-reducing sugars content while the values of reducing sugars increased. The electrical conductivity, potassium leaching and fatty acidity increased significantly with the rise of temperature and potassium leaching reduced with increasing of the pre-drying period. The fatty acidity test showed to be sensible to the drying temperature.
Efficiency of fatty acidity test on the evaluation of the quality of arabic coffee (C.A) submitted to different dry periods and temperatures
Keywords: Drying; parchment coffee; drink; Coffea arabica L.